2020
DOI: 10.31487/j.nnb.2020.03.03
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of Rat Brain After Treatment with Phenelzine: High-Resolution Mass Spectrometric Demonstration of Increased Brain Levels of N-Acetyl Amino Acids

Abstract: Background: Phenelzine (PLZ) is a non-specific monoamine oxidase inhibitor that has demonstrated clinical efficacy in patients with treatment resistant depression. The mechanism of action with regard to this efficacy is complicated in that its metabolite, β-phenylethylidenehydrazine (PEH), is an inhibitor of amino acid transaminases resulting in dramatic brain elevations of GABA, alanine, ornithine and tyrosine. The full neurochemical profile of PLZ and PEH remain to be explored. Objective: To undertake a non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…In metabolomics studies, we also found that ip treatment of male rats with PLZ or PEH resulted in marked increases in brain cortex levels of ornithine (MacKenzie et al 2008b ) and a number of N-acetylated amino acids (Wood et al 2020 ). We speculated that the increased ornithine levels may be an indicator of decreased formation of glutamate and/or polyamines (resulting in decreased formation of reactive aldehydes such as acrolein and 3-AP), thus contributing to neuroprotection.…”
Section: Other Neurobiological Findings With Plz That May Have Relevance To Neuroprotectionmentioning
confidence: 91%
“…In metabolomics studies, we also found that ip treatment of male rats with PLZ or PEH resulted in marked increases in brain cortex levels of ornithine (MacKenzie et al 2008b ) and a number of N-acetylated amino acids (Wood et al 2020 ). We speculated that the increased ornithine levels may be an indicator of decreased formation of glutamate and/or polyamines (resulting in decreased formation of reactive aldehydes such as acrolein and 3-AP), thus contributing to neuroprotection.…”
Section: Other Neurobiological Findings With Plz That May Have Relevance To Neuroprotectionmentioning
confidence: 91%